A handbook of indigo dyeing - Prideaux, Vivien (Tunbridge Wells, Kent, [England] Search Press Limited, 2003)
Introduction: History ; Healthy and safety -- Materials: fibres : Indigo : Other materials -- Preparing fabric: Pre-washing : Shibori: itajime -- board clamping : kikko folding : stitched and gathered shibori : binding objects into fabric : folded and stitched shibori : bomaki -- pole wrapping : katano : paste resist -- Methods of dyeing: The zinc lime vat : The hydrosulphite vat : Dyeing yarn : Other recipes : Post-dyeing treatments -- Projects: Silk velvet scarf : Tea cosy : Bog jacket : Cushion.
Includes bibliographical references (page 95) and index.
Keywords: Indigo; Dyes and dyeing -- Technique